Changing the balance of social care for older people: simulating scenarios under demographic ageing in New Zealand. (6th October 2016) - Lay‐Yee, Roy; Pearson, Janet; Davis, Peter; von Randow, Martin; Kerse, Ngaire; Brown, Laurie
Abstract: The demographic ageing of New Zealand society, as elsewhere in the developed world, has dramatically increased the proportion of older people (aged 65 years and over) in the population. This has major policy implications for the future organisation of social care. Our objective was to test the effects on social care use, first, of putative changes in the overall disability profile of older people, and second, of alterations to the balance of their care, i.e. whether it was community‐based or residential. In order to undertake these experiments, we developed a microsimulation model of the later life course using individual‐level data from two official national survey series on health and disability, respectively, to generate a synthetic version which replicated original data and parameter settings. A baseline projection under current settings from 2001 to 2021 showed moderate increases in disability and associated social care use. Artificially decreasing disability levels, below the baseline projection, only moderately reduced the use of community care (both informal and formal). Scenarios implemented by rebalancing towards informal care use moderately reduced formal care use. However, only moderate compensatory increases in community‐based care were required to markedly decrease the transition to residential care. The disability impact of demographic ageing may not have a major negative effect on system resources in developed countries like New Zealand. As well as healthy ageing, changing the balance of social care may alleviate the impact of increasing demand due to an expanding population of older people.